2018
DOI: 10.1111/jace.15526
|View full text |Cite
|
Sign up to set email alerts
|

A simple method of short‐term mechanical reliability prediction for ceramics in reactive environments

Abstract: A method is demonstrated for prediction of ceramic reliability limited by fracture in reactive environments. The simplicity of the method relies on the ceramic displaying ideal indentation‐strength behavior and on the applied loading leading to short‐term power‐law crack velocity behavior. Reactive failure strength measurements, treating flaw size as a variable and failure time as a constraint in a “pass‐fail” test, enable reliability, including both intrinsic and contact flaws, to be predicted. Little to no c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A subsequent experimental work omitted microstructural effects and showed that constant stressing‐rate loading and long‐term zero‐stress aging in moderately corrosive environments could significantly affect reliability predictions through flaw alteration effects. Another work simplified consideration even further by omitting all effects of microstructure, contact‐flaw alteration, and crack‐velocity thresholds, to demonstrate a method for short‐term reliability prediction in reactive environments for components under constant applied stress containing contact flaws. In the work here, different simplifications are made to arrive at long‐term analytical reliability predictions: Microstructural effects and contact‐flaw stress fields are omitted, components containing simple cracks under constant applied stress are considered, but the crack‐velocity threshold in the reactive environment is included.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A subsequent experimental work omitted microstructural effects and showed that constant stressing‐rate loading and long‐term zero‐stress aging in moderately corrosive environments could significantly affect reliability predictions through flaw alteration effects. Another work simplified consideration even further by omitting all effects of microstructure, contact‐flaw alteration, and crack‐velocity thresholds, to demonstrate a method for short‐term reliability prediction in reactive environments for components under constant applied stress containing contact flaws. In the work here, different simplifications are made to arrive at long‐term analytical reliability predictions: Microstructural effects and contact‐flaw stress fields are omitted, components containing simple cracks under constant applied stress are considered, but the crack‐velocity threshold in the reactive environment is included.…”
Section: Discussionmentioning
confidence: 99%
“…In the work here, different simplifications are made to arrive at long‐term analytical reliability predictions: Microstructural effects and contact‐flaw stress fields are omitted, components containing simple cracks under constant applied stress are considered, but the crack‐velocity threshold in the reactive environment is included. In addition, the works cited made deterministic reliability predictions as only mean responses were considered. Here, probabilistic reliability predictions are made as the distribution of responses is considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation